2021
DOI: 10.1002/hed.26724
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery versus nonrobotic resection of oropharyngeal squamous cell carcinoma

Abstract: The aim of this study is to evaluate the impact of transoral robotic surgery (TORS) compared to nonrobotic surgery (NRS) on overall survival in oropharyngeal squamous cell carcinoma (OPSCC). We performed a retrospective study of patients with HPV+ and HPV− OPSCC undergoing TORS or NRS with neck dissection using the National Cancer Database from the years 2010–2016. Among patients with OPSCC in our cohort, 3167 (58.1%) patients underwent NRS and 2288 (41.9%) underwent TORS. TORS patients demonstrated better ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Finally, the rate of pathologic ECE observed among patients treated with TORS was 25%, which is also noteworthy. Although this rate of ECE is relatively high in comparison with SCC of other head and neck subsites, similarly high rates of pathologic ECE have been reported by other national studies of surgically treated OPSCC (23%‐31%) 24,25 . Interestingly, a recent meta‐analysis of HPV‐related OPSCC found that the T stage, the number of nodal metastases, lymphovascular invasion, and perineural invasion were associated with higher rates of disease recurrence but not ECE 26 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Finally, the rate of pathologic ECE observed among patients treated with TORS was 25%, which is also noteworthy. Although this rate of ECE is relatively high in comparison with SCC of other head and neck subsites, similarly high rates of pathologic ECE have been reported by other national studies of surgically treated OPSCC (23%‐31%) 24,25 . Interestingly, a recent meta‐analysis of HPV‐related OPSCC found that the T stage, the number of nodal metastases, lymphovascular invasion, and perineural invasion were associated with higher rates of disease recurrence but not ECE 26 .…”
Section: Discussionsupporting
confidence: 61%
“…Although this rate of ECE is relatively high in comparison with SCC of other head and neck subsites, similarly high rates of pathologic ECE have been reported by other national studies of surgically treated OPSCC (23%-31%). 24,25 Interestingly, a recent metaanalysis of HPV-related OPSCC found that the T stage, the number of nodal metastases, lymphovascular invasion, and perineural invasion were associated with higher rates of disease recurrence but not ECE. 26 Whether ECE should be considered an indication for the addition of adjuvant systemic therapy in surgically treated HPV-related OPSCC remains an important ongoing area of research.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In multiple national studies, TORS has been associated with reduced margin positivity and improved OS in patients with OPC versus other surgical approaches. 15,27 The positive margin rate in this cohort was very favorable at 13.7%. Nguyen et al postulated the survival benefit may be due to the technical advantages of TORS including improved visualization angles, magnified views, increased range of motion, and ability to use en bloc resection techniques.…”
Section: Discussionmentioning
confidence: 72%
“…However, minimally invasive techniques are associated with significantly less morbidity than the traditional approaches and may optimize oncologic outcomes, as well 25,26 . In multiple national studies, TORS has been associated with reduced margin positivity and improved OS in patients with OPC versus other surgical approaches 15,27 . The positive margin rate in this cohort was very favorable at 13.7%.…”
Section: Discussionmentioning
confidence: 79%
“…They showed that TORS had a lower rate of tracheotomy during treatment (3.9% vs. 11.4%) and post-treatment gastrostomy tube use (21.9% vs. 34.2%) than non-robotic surgery ( 16 ). Furthermore, a retrospective cohort study using de-identified data from the National Cancer Database from 2010 to 2016 by Chillakuru et al, comparing TORS (N=2288) with non-robotic surgery (N=3167), showed that patients who underwent TORS had better OS rates than those who underwent non-robotic surgery regardless of human papillomavirus status ( 17 ). After TORS using the da Vinci Robotic Surgical System (Intuitive Surgical) was approved by the United States Food and Drug Administration in 2009, TORS has now spread nationwide for the treatment of pharyngeal and laryngeal cancer in the United States.…”
Section: Treatment Outcomes Of Torsmentioning
confidence: 99%